Association between dairy intake and gastric cancer: a meta-analysis of observational studies. - Shu-bo Tian; Jian-chun Yu; Wei-ming Kang; Zhi-qiang Ma; Xin Ye; Zhan-jiang Cao (PLoS ONE)
Purpose Observational studies have given inconsistent findings on the relationship between intake of dairy products and gastric cancer. We therefore conducted a systematic review with a meta-analysis of observational studies to summarize available evidence on this point. Methods We searched the electronic literature databases of PubMed (Medline), EMBASE and the Chinese Biomedical Literature Database up until August 30, 2013. All studies were limited to the English language. Random-effects models were used to pool study results between dairy products consumption and the risk of gastric cancer. We also performed subgroup, publication bias and sensitivity analysis. Results Eight prospective studies and 18 case-control studies were included in our analysis, with a total number of 7272 gastric cancer cases and 223,355 controls. Pooled relative risks of all studies showed no significant association between dairy intake and gastric cancer (odds ratio [OR]: 1.09, 95% confidence interval [CI]: 0.96-1.25). When study design was separately analyzed, population-based case-control studies showed a positive association between dairy intake and gastric cancer risk (OR: 1.36; 95% CI: 1.07-1.74), whereas no associations were shown by hospital-based case-control studies (OR: 0.86, 95% CI: 0.72-1.02) or cohort studies (OR = 1.01, 95% CI = 0.91-1.13). Conclusions The meta-analysis shows that no clear association apparently exists between consumption of dairy products and gastric cancer risk. Further well-designed cohort and intervention studies should be conducted to verify this lack of association.